Geography and trends of developing ethnic festival tourism in the Ukrainian Part of the Carpathian Euroregion - Topornytska, Maria Jaroslavivna (Journal of Education, Health and Sport, 2015)
Topornytska Maria. Geography and trends of developing ethnic festival tourism in the Ukrainian Part of the Carpathian Euroregion. Journal of Education, Health and Sport. 2015;5(7):461-474. ISSN 2391-8306. DOI 10.5281/zenodo.21047 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A461-474 https://pbn.nauka.gov.pl/works/591907 http://dx.doi.org/10.5281/zenodo.21047 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 15.07.2015. GEOGRAPHY AND TRENDS OF DEVELOPING ETHNIC FESTIVAL TOURISM IN THE UKRAINIAN PART OF THE CARPATHIAN EUROREGION Maria Topornytska* *Ivan Franko National University of Lviv, Ukraine 41, Doroshenko St., UA – 79000 L’viv, Ukraine, Topornytska_Maria@i.ua Abstract Ethnic festivals are the motive basis as well as a resource of tourism, hence they are the object of studying the geography of tourism. Their development is of great importance for the region, results in new tourist destinations and growth of income in the countryside. The statistics proves that more and more tourists are coming to the region due to ethnic festivals. The number of ethnic festivals is increasing and their geography is expanding. Over 2000 - 2011 (in the pre-crises period of the state’s development) the number of ethnic festivals in the Ukrainian part of the Carpathian Euroregion grew from 55 to 228. About 100 new popular tourist destinations appeared in the tourist map. The article describes geographic, ethno-cultural and organizational principles of ethnic festival tourism development in the Carpathian region of Ukraine. Key words: ethnic tourism, festival, ethnic festival tourism, regional development, geography of ethnic festivals.